HUBUNGAN TINGKAT PENGETAHUAN DAN KEPATUHAN PERAWAT TERHADAP PENERAPAN FIVE MOMENT HAND HYGIENE DI RUMAH SAKIT AISYIYAH PARIAMAN - DORA, MECHI SILVIA; ARMAITA, ARMAITA; BAKRI, LATHIFA KARIMA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Five moments hand hygiene is influenced by various things such as knowledge and compliance of nurses. The purpose of this study was to determine the relationship between the level of knowledge and compliance of nurses by implementing five moments hand hygiene in the Inpatient Room of Aisyiyah Pariaman Hospital. The design of this study was descriptive correlative with a cross-sectional approach. The research variables were knowledge and compliance with the implementation of five moments hand hygiene. The research sample was taken by total sampling of 31 nurses at Aisyiyah Pariaman Hospital. Data collection was carried out using questionnaires and observation sheets. Data were analyzed using Chi Square at alpha = 5%. The results showed that most nurses had a good level of knowledge (83.9%) and almost all nurses had a good level of compliance (83.9%) with five moments hand hygiene (83.9%). The results of the chi square test showed that there was a relationship between the level of knowledge of nurses and compliance with five moments hand hygiene (ρ = 0.00 and there was a relationship between compliance with five moments hand hygiene (ρ = 0.00). In conclusion, the level of knowledge is related to nurse compliance with five moments hand hygiene in the inpatient room of Aisyiyah Pariaman Hospital.